2018
DOI: 10.1021/acssynbio.8b00127
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the 5′ UTR-Mediated Regulation of Protein Abundance in Yeast Using Nucleotide Sequence Activity Relationships

Abstract: The 5′ untranslated region (5′UTR) plays a key role in post-transcriptional regulation, but interaction between nucleotides and directed evolution of 5′UTRs as synthetic regulatory elements remain unclear. By constructing a library of synthesized random 5′UTRs of 24 nucleotides in Saccharomyces cerevisiae, we observed strong epistatic interactions among bases from different positions in the 5′UTR. Taking into account these base interactions, we constructed a mathematical model to predict protein abundance with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…The initiation mechanisms in the 5 0 UTR in eukaryotes seem more diverse and complicated than do those for prokaryotes. However, recent studies have shown that the 5 0 UTR sequence has great potential for tuning the expression in eukaryotes, such as S. cerevisiae or Chinese hamster ovary-S (CHO-S) cells (Ding et al, 2018;Petersen et al, 2018;Weenink et al, 2018). These studies provided modular 5 0 UTRs designs that work relatively well with low-context dependence on the downstream ORF.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The initiation mechanisms in the 5 0 UTR in eukaryotes seem more diverse and complicated than do those for prokaryotes. However, recent studies have shown that the 5 0 UTR sequence has great potential for tuning the expression in eukaryotes, such as S. cerevisiae or Chinese hamster ovary-S (CHO-S) cells (Ding et al, 2018;Petersen et al, 2018;Weenink et al, 2018). These studies provided modular 5 0 UTRs designs that work relatively well with low-context dependence on the downstream ORF.…”
Section: Reviewmentioning
confidence: 99%
“…Likewise, successful 5 0 UTR prediction algorithms based on multiple regression or machine learning approaches have been developed for yeast (Cuperus et al, 2017;Decoene et al, 2018;Ding et al, 2018). Such big-data analyses, based on randomized sequence libraries, seem a promising road toward better predictive algorithms for robust regulation of synthetic genes.…”
Section: Randomization Smart Selection and Machine Learningmentioning
confidence: 99%
“…Features may also be inferred from the original sequence, for example using biophysical models yielding free energy of the 5′-UTR [9,45,54,55], or hybridization energy and target accessibility of miRNA in the 3′-UTR [56]. An important feature is nucleosome occupancy [39,[57][58][59], which has been used to facilitate terminator design [60].…”
Section: Data Encoding and Model Trainingmentioning
confidence: 99%
“…It was also demonstrated that the obtained model could be used for the forward engineering of 5 UTRs as regulatory elements for synthetic pathways. Ding et al (2018) developed a regression model with a prediction precision of 60%, which was then used as basis for an improved model based on nucleotide sequence activity relationships (NuSAR). After multiple iterative cycles of designing, screening and model reconstruction, the final model was able to explain 71% of the variation in protein synthesis.…”
Section: Predicting the Relationship Between 5 Utrs And Protein mentioning
confidence: 99%